نظرية الظروف الطارئة في الفقه الإسلامي و القانون المدني الجزائري - سمية عويشات, ياسمينة ذباح (جامعة محمد بوضياف /كلية العلوم الإنسانية والاجتماعية, 2020)
يقر كل من الفقه الإسلامي والقانون المدني الجزائري على مبدأ العقد شريعة المتعاقدين، وعلى كل من المتعاقدين تنفيذه بحسن نية، ولا يجوز نقضه أو تعديله إلا باتفاق الطرفين، إلا أن هذا المبدأ ليس مطلقا في حالة الظروف الطارئ والتي مقتضاها أنه إذا ما طرأ بعد إبرام العقد وقبل تنفيذه حوادث لم تكن متوقعة و أصبح التزام أحد المتعاقدين مرهقا، و يهدده بخسارة فادحة جاز للقاضي في هذه الحالة أن يعدل العقد، ويرد الالتزام المرهق للحد المعقول.Both Islamic jurisprudence and Algerian civil law recognize the principle of the contract as the law of the contractors, and each of the contractors must implement it in good faith, and may not be revoked or amended except by the agreement of the parties, but this principle is not absolute in the case of the circumstances of the emergency and which is required that if the conclusion of the contract and before its implementation occurs accidents that were not anticipated and the obligation of one of the contractors becomes cumbersome, and threatens it with a heavy loss in this case the judge may amend the contract, and the burdensome obligation to the reasonable extent is returned keywords: emergency circumstances، power of judge ،contractors modification of contract weary commitment.
Keywords: الظروف الطارئة، سلطة القاضي،المتعاقدين، تعديل العقد، الالتزام المرهق،